Chemical studies of 1,5-benzodioxepanones - Gelebe, Aifheli Carlson (Rhodes University, Faculty of Science, Department of Chemistry, 1991)
Chromone and flavanone derivatives were prepared by condensation of the corresponding 2-hydroxyacetophenones (with diethyl oxalate or the appropriate aromatic aldehyde respectively) and cyclisation of the condensation products. Saeyer-Villiger rearrangement of these flavanones, with MCPBA, resulted in expansion of the C-ring. Spectroscopic techniques have been used to establish the regioselectivity of the rearrangement and hence, the identity of the rearranged products as 1,5-benzodioxepan-4-ones. The 1,5-benzodioxepan-4-ones were subjected to detailed ¹H and ¹³C n.m.r. analysis and a combination of low and high resolution mass spectrometry has been used to study the mass fragmentation pathways of these ring-expanded products.
Keywords: Biochemistry; Pigments (Biology); Benzopyrans